2023
DOI: 10.1186/s13024-023-00634-3
|View full text |Cite
|
Sign up to set email alerts
|

Axonal energy metabolism, and the effects in aging and neurodegenerative diseases

Abstract: Human studies consistently identify bioenergetic maladaptations in brains upon aging and neurodegenerative disorders of aging (NDAs), such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, and Amyotrophic lateral sclerosis. Glucose is the major brain fuel and glucose hypometabolism has been observed in brain regions vulnerable to aging and NDAs. Many neurodegenerative susceptible regions are in the topological central hub of the brain connectome, linked by densely interconnected long-range axo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 426 publications
(405 reference statements)
0
7
0
Order By: Relevance
“…Recent investigations have revealed that mitochondrial dynamics and their structural adaptations can influence neuronal health, synaptic plasticity, and overall cognitive performance 3 6 . Proper mitochondrial function is essential for sustaining neural activities, while its dysfunction may lead to neurodegenerative diseases and cognitive impairments 7 9 . Mitochondria typically have an elongated shape, delimited by smooth outer and complex inner membranes 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have revealed that mitochondrial dynamics and their structural adaptations can influence neuronal health, synaptic plasticity, and overall cognitive performance 3 6 . Proper mitochondrial function is essential for sustaining neural activities, while its dysfunction may lead to neurodegenerative diseases and cognitive impairments 7 9 . Mitochondria typically have an elongated shape, delimited by smooth outer and complex inner membranes 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, synapses represent the main locations where ATP is consumed [10]. The reason why only about half of the presynaptic release sites contain a stationary mitochondrion remains a mystery, while the remaining sites lack one [11][12][13][14]. The question of how a bouton without a stationary mitochondrion obtains its supply of ATP is investigated in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have revealed that mitochondrial dynamics and their structural adaptations can in uence neuronal health, synaptic plasticity, and overall cognitive performance [3][4][5][6] . Proper mitochondrial function is essential for sustaining neural activities, while its dysfunction may lead to neurodegenerative diseases and cognitive impairments [7][8][9] . Mitochondria typically have an elongated shape, delimited by smooth outer and complex inner membranes 10 .…”
Section: Introductionmentioning
confidence: 99%